Makna “Menyesallah Allah” Dalam Kitab Yunus 3:10 dan Relevansinya dalam Pendidikan Jemaat - Jacobus, Herry Reinhard; Nainggolan, Bartolomeus Diaz (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
The use of the word God regrets in Jonah 3:10 often seems to confuse Bible readers, because it contradicts God's omniscient nature. This raises the question of whether God's omniscience is just a context or whether it is really God's nature like that. This paper aims to explain and provide an understanding of the word regret in Jonah 3:10. By using the method of interpretation as well as searching through books and articles, we will analyze the word regret in the book of Jonah 3:10. Jonah was repeatedly told by God to remind them to repent, because God knew that they would repent. That is why God was sorry because He is omniscient. God is merciful and His love is no respecter of persons, even the most sinful people will be forgiven by God. The book of Jonah 3:10 is a testament to God's character.